Rapidly progressive osteoarthritis in the medial patellar facet due to lateral femoral placement after medial unicompartmental knee arthroplasty. A case report. (November 2021) - Inoue, Shinji; Hashimoto, Kazuhiko; Yamagishi, Kotaro; Nakagawa, Koichi; Akagi, Masao
Abstract: Introduction and importance: Factors that affect patellofemoral (PF) osteoarthritis (OA) after unicompartmental knee arthroplasty (UKA) remain unclear. We report a case in which the lateral placement of the femoral component resulted in rapidly progressive OA in the medial patellar facet. Case presentation: The patient was an 84-year-old woman who had increased pain in the left knee due to varus knee OA for 1 year and underwent medial UKA. One month after the surgery, the patient complained of limited knee flexion of 90° with anterior knee pain, and around 7-mm lateral placement of the femoral component was observed on a postoperative radiograph and computed tomography scan. Six months after the surgery, rapidly progressive OA with subchondral bone depression in the medial facet was observed and this has been ongoing till the last follow-up of 3 years. The knee flexion is limited 105° now, and the patient complains of quadriceps weakness with anterior knee pain when stair-climbing and standing up from a chair. Clinical discussion: Lateral placement of the femoral component in medial UKA may cause progressive PF OA with limited knee flexion and anterior knee pain, which could be attributed to impingement between the femoral component and the medial patellar facet. Conclusion: Surgeons should be careful regarding the lateral placement to prevent symptomatic PF OA from occurring after medial UKA. Highlights: Factors that affect patellofemoral (PF) osteoarthritis (OA) after UKA have been rarely reported. An 84-year-old woman with rapidly progressive symptomatic PF OA after medial UKA is presented. Impingement between the femoral component placed laterally and the medial patellar facet seems attributable to the PF OA. The lateral placement would be one of risk factors for PF OA after medial UKA.